(5x-2)-(6-2x)=x-9+5x

Simple and best practice solution for (5x-2)-(6-2x)=x-9+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-2)-(6-2x)=x-9+5x equation:


Simplifying
(5x + -2) + -1(6 + -2x) = x + -9 + 5x

Reorder the terms:
(-2 + 5x) + -1(6 + -2x) = x + -9 + 5x

Remove parenthesis around (-2 + 5x)
-2 + 5x + -1(6 + -2x) = x + -9 + 5x
-2 + 5x + (6 * -1 + -2x * -1) = x + -9 + 5x
-2 + 5x + (-6 + 2x) = x + -9 + 5x

Reorder the terms:
-2 + -6 + 5x + 2x = x + -9 + 5x

Combine like terms: -2 + -6 = -8
-8 + 5x + 2x = x + -9 + 5x

Combine like terms: 5x + 2x = 7x
-8 + 7x = x + -9 + 5x

Reorder the terms:
-8 + 7x = -9 + x + 5x

Combine like terms: x + 5x = 6x
-8 + 7x = -9 + 6x

Solving
-8 + 7x = -9 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-8 + 7x + -6x = -9 + 6x + -6x

Combine like terms: 7x + -6x = 1x
-8 + 1x = -9 + 6x + -6x

Combine like terms: 6x + -6x = 0
-8 + 1x = -9 + 0
-8 + 1x = -9

Add '8' to each side of the equation.
-8 + 8 + 1x = -9 + 8

Combine like terms: -8 + 8 = 0
0 + 1x = -9 + 8
1x = -9 + 8

Combine like terms: -9 + 8 = -1
1x = -1

Divide each side by '1'.
x = -1

Simplifying
x = -1

See similar equations:

| -4x-8x+17=23 | | 4(2x-7)=128 | | 2-(3/4)z=(1/8)z+9 | | 20-n=18 | | 42=6-2x | | 35+n=4n+7(5n+5) | | W+76+w=129 | | (9x)/(6x-11) | | 8=x-1+2x | | ((9x)/(6x-11)) | | 13a-7= | | 2x+1500=x+1000 | | (1/2x+3/4)+(1/2x-1/4) | | 6x+8y=2 | | (3t)/(t-2)(3t-6)/(t^2) | | 8(3x+1)= | | (9x)/6x-11 | | (x-5)+17=15 | | 15x+45=75 | | 5z-13=-3 | | x*5=x+150 | | 3(j-k)= | | (9x)/6x-1 | | N+10=6-8n | | 5-2x=3x-2 | | N-10=8n-6 | | -2x+4=2+8 | | 5x+3x=28 | | 4x+2=6-x | | 10-n=6-8n | | 9.10-0.8= | | 3(3.30+2.50)=55.20 |

Equations solver categories